QSAR Study of Some Natural and Synthetic Platelet Aggregation Inhibitors and their Pharmacological Profile - Valery M. Dembitsky, Tatyana A. Gloriozova, Vladimir V. Poroikov, Maju M. Koola (Journal of Applied Pharmaceutical Science, 2022)
Several well-known synthetic drugs, such as aspirin, elinogrel, and beraprost, and natural drugs, such as eptifibatide and vorapaxar, as platelet aggregation inhibitors are widely used in clinical medicine today. The purpose of this review is a comparative pharmacological analysis of the biological activity of these drugs with natural sulfur-containing hydrocarbons isolated from bacteria, plants, and mineral oils. According to the quantitative structure–activity relationship estimates, these naturally occurring sulfur-containing hydrocarbons are more likely to exhibit antiplatelet properties than those currently used in clinical medicine.
Keywords: Antiplatelet, synthetic, natural, drugs, aspirin, aggregation, platelet, thrombin, inhibitors, PASS predictions